Role of free volumes in conducting properties of GO and rGO filled PVA-PEDOT:PSS composite free standing films: A positron annihilation lifetime study. (March 2019) - Hebbar, Vidyashree; Bhajantri, R.F.; Ravikumar, H.B.; Ningaraju, S.
Abstract: In this paper, we demonstrate the preparation of the polymer composite films of poly (vinyl alcohol) (PVA) – poly (3, 4-ethylene dioxythiophene):polystyrene sulfonate (PEDOT:PSS) blend filled with synthesized Graphene oxide (GO) and reduced Graphene oxide (rGO) by solvent casting technique. The X-ray diffraction (XRD) studies confirmed the changes in crystallinity upon incorporation of the Graphene. The differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) depicted the variation in chain mobility and thermal stability of the GO/rGO filled composites. The scanning electron microscope (SEM) and atomic force microscope (AFM) studies affirm the uniform dispersion of fillers in the polymer matrix. The mechanical properties such as the Young's modulus and tensile strength are enhanced after the insertion of fillers. The impedance data is fitted with the equivalent circuit model and the obtained impedance parameters execute the variation in bulk conductivity with increase in wt.% of filler and is maximum at 5 wt.% GO/rGO addition. Positron annihilation lifetime spectroscopy (PALS) is effectively used to investigate the molecular packing and hence free volume properties of the composites. The o-Ps lifetime and hence, the size of the free volume is initially decreased due to shrinkage of free volume and enhanced at 10 wt.% loading, attributed to the increased agglomeration of the additives. The decrease in the lifetime τ 2 and increase in the intensity I 2 at lower filling is attributed to the created small size defects. The variation in the free volume is corroborated by other experimental observations such as XRD, DSC and electrical conductivity. Highlights: PVA-PEDOT:PSS blend composites filled with GO and rGO particles were prepared. Composite films exhibit excellent mechanical strength for 10 wt.% addition of GO particles. PALS study shows that the free-volume variation regulates the conducting properties. The composite with 5 wt.% rGO exhibits highest conductivity.